2022
DOI: 10.1146/annurev-neuro-082321-025137
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Circuits for Locomotion

Abstract: Locomotion is a universal motor behavior that is expressed as the output of many integrated brain functions. Locomotion is organized at several levels of the nervous system, with brainstem circuits acting as the gate between brain areas regulating innate, emotional, or motivational locomotion and executive spinal circuits. Here we review recent advances on brainstem circuits involved in controlling locomotion. We describe how delineated command circuits govern the start, speed, stop, and steering of locomotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 150 publications
3
48
0
Order By: Relevance
“…A longstanding question in neuroscience is how neural circuits flexibly control the limbs during behaviors like walking and reaching. In vertebrate animals, enormous effort has been dedicated to understanding cortical and subcortical circuits that plan movements and issue descending commands (Arber and Costa, 2022; Inagaki et al, 2022; Leiras et al, 2022). There is also an extensive body of literature on the physiology and function of motor neurons (MNs) that directly control muscle activity (Binder et al, 2020; Kernell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A longstanding question in neuroscience is how neural circuits flexibly control the limbs during behaviors like walking and reaching. In vertebrate animals, enormous effort has been dedicated to understanding cortical and subcortical circuits that plan movements and issue descending commands (Arber and Costa, 2022; Inagaki et al, 2022; Leiras et al, 2022). There is also an extensive body of literature on the physiology and function of motor neurons (MNs) that directly control muscle activity (Binder et al, 2020; Kernell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The executing locomotor circuits that control coordinated muscle activity are localized in the spinal cord [1][2][3] , whereas the commands for initiating locomotion reside in supraspinal structures, including the mesencephalic locomotor region (MLR), which control the start and speed of locomotion [4][5][6][7][8][9][10][11] . Reticulospinal command neurons integrate the signals from the MLR before they activate spinal executing locomotor circuits 5,[11][12][13][14] .…”
mentioning
confidence: 99%
“…Direct ascending proprioceptive afferents convey in the cuneate and gracile nuclei of the dorsal column. In the cat, it has been shown that intra‐cuneate networks are responsible for the potentiation of proprioceptive feedback from the forelimb and that cuneate cells project to the reticular formation and the mesencephalic locomotor region (Leiras et al., 2010), with both known to have key roles in the initiation, control and termination of locomotion (Caggiano et al., 2018; Cregg et al., 2020; Grillner & El Manira, 2020; Leiras et al., 2022). To further elucidate the specific roles of the aforementioned structures in the regulation of proprioceptive information during locomotion, additional experiments are certainly needed.…”
Section: Discussionmentioning
confidence: 99%